INDONESIA'S CHAIRMANSHIP OF ASEAN 2023: ADVANCING REGIONAL COLLABORATION ON ENVIRONMENTAL DIPLOMACY - Listianto, Karunya Saka (Jurusan Ilmu Hubungan Internasional, 2025)
Indonesia, as the chair of ASEAN in 2023, focused on promoting ASEAN as a fast-growing, inclusive, and sustainable economic region with the theme